Survey of surgical specialists' content preferences in radiology reports for extrahepatic portosystemic shunts. Issue 3 (8th March 2019) - Plested, Mark J.; Drees, Randi
Abstract: The aim of this prospective, survey study was to assess the opinions of specialist surgeons as to the preferred content, nomenclature, and classification of extrahepatic portosystemic shunts for inclusion in radiology reports. A link to an online survey was sent by email to members of the European College of Veterinary Surgeons and the Association of Veterinary Soft Tissue Surgeons, and was made available on the American College of Veterinary Surgeons web forum and Facebook page. There were 93 respondents (survey sent to over 2500 email addresses and made available in two online locations). Most respondents agreed that they both review the images themselves (87/92, 95%) and read the radiology report (82/92, 89%) prior to surgery. Most respondents believed that the radiology report should contain a detailed anatomic description of the insertion (83/92, 90%), origin (54/91, 59%), and course (70/92, 76%) of the shunt, as well as a measure of the diameter of the shunting vessel at its insertion (54/92, 59%). Most respondents (70/90, 78%) disagreed that a brief description of shunt type, such as portocaval or portophrenic, was sufficient. Respondents were undecided regarding the use of an alphanumeric classification system (36/92, 39% agree; 32/92, 35% disagree). There was agreement that details of the presence or absence of urolithiasis (91/93, 98%), renomegaly (54/93, 58%), and peritoneal fluid (72/92, 78%) should be included in the report. The results of this study will help to guide reporting radiologists in providing descriptions of extrahepatic portosystemic shunts that include information most preferred by the recipient surgeons.